Nilai integritas melalui pembelajaran matematika bagi mahasiswa pendidikan matematika - Jamiah, Yulis; Salsabila HS, Kintan; Supriyadi, Dede (International Journal of Progressive Mathematics Education, 2025)
Integrity Values are a unity between mindset, feelings or sensations felt, speech and behavior that are in harmony with conscience and applicable norms. This study aims to internalize students integrity values through a humanist mathematics learning model, so that students have personalities that can strengthen a high level of honesty and ethics in their words and actions. This goal is achieved by involving a cyclical process starting from conceptual learning model assessment to implementation and evaluation. The subjects of this study were 68 students from two classes. The identification of field problems, reviewing and validating the learning model, exploration of integrity values, identification of field problems, reviewing and validating the learning model, and implementing De model trofi real action research. The results showed the percentage of value in everything the learning model was 88,3% which is categorized as very good and 100% of students gave a very positive response to humanist mathematics learning that internalizes integrity values. These findings indicate that the humanist approach is effective in building an inclusive learning climate but requires additional strategies to strengthen task precision. This research contributes significantly to formulating a mathematical pedagogical model that aligns numerical logic acumen with moral resilience as competency standards for future teachers.   Nilai integritas merupakan kesatuan antara mindset, perasaan atau sensasi yang dirasakan, ucapan maupun perilaku yang selaras dengan hati nurani dan norma yang berlaku. Penelitian ini bertujuan menginternalisasikan nilai integritas mahasiswa melalui model pembelajaran dalam perkataan dan tindakannya. Tujuan tersebut dicapai yang melibatkan proses siklus mulai dari pengkajian model pembelajaran secara konseptual hingga implementasi dan evaluasi. Subjek penelitian ini berjumlah 68 mahasiswa berasal dari dua kelas. Prosedur penelitian meliputi analisis teoritis model pembelajaran, eksplorasi nilai-nilai integritas, identifikasi masalah lapangan, mengkaji dan validasi model pembelajaran, serta implementasi model melalui penelitian tindakan nyata. Hasil penelitian menunjukkan bahwa nilai persentase dalam menerapkan model pembelajaran adalah 88,3% yang berkategori sangat baik, dan 100% mahasiswa memberikan respon sangat positif terhadap pembelajaran matematika humanis yang menginternalisasikan nilai integritas. Temuan ini mengindikasikan bahwa pendekatan humanis efektif berkontribusi signifikan dalam merumuskan model pedagogi matematika yang menyelaraskan ketajaman logika numerik dengan ketangguhan moral sebagai standar kompetensi guru masa depan.